Zearalenone exacerbates lipid metabolism disorders by promoting liver lipid droplet formation and disrupting gut microbiota - Xiao Han; Bingxin Huangfu; Tongxiao Xu; Kunlun Huang; Xiaoyun He (Ecotoxicology and Environmental Safety)
Zearalenone (ZEA), produced by Fusarium, is a fungal toxin commonly found in maize, wheat, and other cereals. ZEA has the ability to bind to estrogen receptors of humans and animals and is an environmental endocrine disruptor that may interfere with glucose homeostasis and lipid metabolism. In this study, we first investigated the effects of chronic exposure to low doses of ZEA with a high-fat-diet (HFD) in obese C57BL/6 J mice. In the absence of significant toxicity and without affecting glucose tolerance, 50 and 100 μg/kg b. w. ZEA was found to significantly exacerbate lipid synthesis, accumulation and alter the overall transcriptional profile of the liver in mice synergistically with HFD. Validation in combination with AML-12 cells revealed that ZEA promoted lipid synthesis and increased hepatic lipid droplet accumulation via the HNF1β/PPARγ and SREBP1c-HSD17B13/PLINs signal pathways. Further, by analyzing the changes in the intestinal flora of mice and their relationship with lipid metabolism genes, it was found that ZEA decreased the relative abundance of Lactobacillus and increased the relative abundance of Ileococcus, E. faecalis, and Ricardia. These changes were significantly correlated with the expression of Pparg and Srebf1, etc. ZEA may contribute to the abnormality of lipid metabolism by influencing the intestinal microbiota. This study highlights the synergistic effects of long-term low-dose ZEA and excess lipids, providing a theoretical basis for elucidating the mechanism of chronic toxicity of ZEA and its negative impact on metabolic diseases.